Role of Cdc23/Mcm10 in generating the ribonucleotide imprint at the mat1 locus in fission yeast - Singh, Balveer (Nucleic Acids Res, 2019)
The developmental asymmetry of fission yeast daughter cells derives from inheriting ‘older Watson’ versus ‘older Crick’ DNA strand from the parental cell, strands that are complementary but not identical with each other. A novel DNA strand-specific ‘imprint’, installed during DNA replication at the mating-type locus (mat1), imparts competence for cell type inter-conversion to one of the two chromosome replicas. The catalytic subunit of DNA Polymerase α (Polα) has been implicated in the imprinting process. Based on its known biochemical function, Polα might install the mat1 imprint during lagging strand synthesis. The nature of the imprint is not clear: it is either a nick or a ribonucleotide insertion. Our investigations do not support a direct role of Polα in nicking through putative endonuclease domains but confirm its indirect role in installing an alkali-labile moiety as the imprint. While ruling out the role of the primase subunit of Polα holoenzyme, we find that mutations in the Polα-recruitment and putative primase homology domain in Mcm10/Cdc23 abrogate the ribonucleotide imprint formation. These results, while confirming the ribonucleotide nature of the imprint suggest the possibility of a direct role of Mcm10/Cdc23 in installing it in cooperation with Polα and Swi1.